The effects of stature, age, gender, and posture preferences on preferred joint angles after real driving. (April 2022) - Wolf, Philipp; Hennes, Nikica; Rausch, Jessica; Potthast, Wolfgang
Abstract: Few studies have investigated preferred driving posture involving real-world driving. For this purpose, seven preferred joint angles of 127 participants were recorded three times from sagittal plane photographs after a short, standardized drive on public roads. Participants' individual driving posture preferences were determined using a word-based questionnaire. The inter- and intraindividual joint angle differences were calculated and some significant effects of stature, age, and gender on these joint angle differences were found. Additionally, significant correlations were found between posture preferences and joint angles, except for the lower extremities. The results show that the factors stature, age, gender, and posture preferences have influence on the preferred joint angles. However, other human-, vehicle-, and context-related factors also seem relevant and should be considered in future studies. The results provide important field-based knowledge for an application-oriented understanding of driving posture and for the human-centered design process of future vehicle interior research and development. Highlights: Capturing preferred driving posture joint angles after real driving. Highest inter- and intraindividual variability observed for elbow and knee flexion. Interindividual driving posture is partly influenced by stature, age, and gender. Stature, age, and gender rarely influence intraindividual joint angle range. Posture preferences partly explain interindividual joint angle differences.